Penilaian Tingkat Kesehatan Keuangan Pada PT. Sumber Tani Agung Gunung Tua - Siregar, Dina; Imsar, Imsar; Hasibuan, Nur Fadhilah Ahmad (Jurnal Manajemen Akuntansi (JUMSI), 2023)
The purpose of this study was to determine the health level of PT. Sumber Tani Agung through analysis of liquidity ratios, solvency, profitability and financial performance from 2018-2021. The research method uses a descriptive qualitative approach. Based on the results of analysis, it can be concluded that the Liquidity Ratio, the Current Ratio, is considered good. The Achid Test Ratio shows that company is able to cover its current debts with its current assets, so that the company is in a liquid state. The Solvency Ratio for 5 years, the Debt Ratio, has decreased very drastically, this is due to the low total debt. The detailed Debt To Equity Ratio is considered good, with a very low current debt value that can still be borne by own capital issued by creditors. Profitability ratio, the return on assets is considered good, due to an increase in the ratio every year.